Global Warming and Its Impact on Indian Economy: An Assessment (Economic Journal of Nepal, 2013)
This paper attempts to highlight the impact of global warming on Indian economy. The results indicate that greenhouse gases are basically responsible for global warming. It is a worldwide problem. It will affect every sector of the economy i.e. agricultural, industrial and service sector. Employment generation in these sectors will be hampering. As a result of global warming poverty, unemployment, illegal activities, migration, slum areas, diseases, flood, drought will increase. Biodiversity and economic balance will be disturbed. Government will need more fund for disaster management purpose. Thus, the paper suggests that government should take proper steps for mitigating the effects of global warming on the economy.